Lewis acid catalysis of phosphoryl transfer from a copper(II)-NTP complex in a kinase ribozyme - Biondi, Elisa (Oxford University Press, 2013)
The chemical strategies used by ribozymes to enhance reaction rates are revealed in part from their metal ion and pH requirements. We find that kinase ribozyme K28(1-77)C, in contrast with previously characterized kinase ribozymes, requires Cu(2+) for optimal catalysis of thiophosphoryl transfer from GTPγS. Phosphoryl transfer from GTP is greatly reduced in the absence of Cu(2+), indicating a specific catalytic role independent of any potential interactions with the GTPγS thiophosphoryl group. In-line probing and ATPγS competition both argue against direct Cu(2+) binding by RNA; rather, these data establish that Cu(2+) enters the active site within a Cu(2+)•GTPγS or Cu(2+)•GTP chelation complex, and that Cu(2+)•nucleobase interactions further enforce Cu(2+) selectivity and position the metal ion for Lewis acid catalysis. Replacing Mg(2+) with [Co(NH(3))(6)](3+) significantly reduced product yield, but not k(obs), indicating that the role of inner-sphere Mg(2+) coordination is structural rather than catalytic. Replacing Mg(2+) with alkaline earths of increasing ionic radii (Ca(2+), Sr(2+) and Ba(2+)) gave lower yields and approximately linear rates of product accumulation. Finally, we observe that reaction rates increased with pH in log-linear fashion with an apparent pKa = 8.0 ± 0.1, indicating deprotonation in the rate-limiting step.